Incorporation of Microreactor Measurements into a Pilot‐Scale Phthalic Anhydride Reactor. Issue 1 (5th November 2014) - Fischer, Nico; Hubach, Patrick; Woll, Christian
Abstract: A major obstacle in the development of industrial catalysts is the scalability of both catalyst performance and synthesis. While utilizing pilot‐scale test reactors allows for a direct transfer from the development stage to the application, it comes at the cost of flexibility. The amount of catalyst required in a pilot‐scale test reactor often surpasses the yields of novel synthesis procedures, requiring extensive scale‐up efforts. Here, pilot‐scale reactors are combined with small lab‐scale reactors, using the example of oxidation of o ‐xylene to phthalic anhydride. Abstract : To overcome problems in scalability of catalyst performance and synthesis during industrial process development, a microreactor was incorporated into a pilot scale multiport phthalic anhydride reactor. It was possible to test small volume model catalysts for their activity and selectivity under various industrially relevant gas compositions.